Substantiating chemical groups for read-across using molecular response profiles - Rosemary E. Barnett; Thomas N. Lawson; Claudia Rivetti; Carlos Barata; Mark T.D. Cronin; Silvia Lacorte; Gavin R. Lloyd; Ralf J.M. Weber; Matthew J. Smith; Andrew D. Southam; Adam Biales; Kara Koehrn; et al. (Regulatory Toxicology and Pharmacology, 2025)

Evaluating the Monro-Kellie Doctrine: Contralateral Hemisphere Shrinkage in Intracerebral Hemorrhage Patients - Elmira Khiabani; Anna C. J. Kalisvaart; Cassandra M. Wilkinson; Peter L. Hurd; Brian H. Buck; Frederick Colbourne (Translational Stroke Research, 2025)

Quantitative insights into the spatio‐temporal variation of Atlantic salmon ( Salmo salar ) biomass in a river catchment using eDNA metabarcoding - William Bernard Perry; Nigel Milner; Ifan Bryn Jâms; Mark de Bruyn; Steve J. Ormerod; Kristy Deiner; Holly M. Bik; Gary Carvalho; John Colbourne; Bernard Jack Cosby; Isabelle Durance; Simon Creer (Journal of Fish Biology, 2025)
Effective species conservation and management requires comprehensive biomonitoring, enhanced by combining traditional and newer methodologies, such as environmental DNA (eDNA) analyses. A seasonal pulse of spawning adult Atlantic salmon ( Salmo salar ) was detected by normalised eDNA 12S reads from metabarcoding, which facilitated estimation of spatial patterns in salmon biomass. A strong relationship was found between normalised reads in the lower section of the River Conwy (Wales, UK) and whole‐river adult biomass (estimated from rod catch data and a fish counter), explaining 61% of the variation in a linear regression. Moreover, the positive linear relationship between adult biomass and partial effect on normalised reads occurred after the biomass estimate exceeded 1500 kg, indicating a threshold where normalised reads become representative of biomass. The relationship observed between normalised reads and biomass, as well as the unique profiles of normalised reads at each of the sites, supports the hypothesis of limited eDNA transport among sampling sites that were 2–4 km apart. River pH showed a significant non‐linear relationship with normalised reads, with a peak in partial effect on normalised reads at pH 6.5. Partial effect on normalised reads also showed a positive linear relationship with flow (discharge), while also peaking at the highest average monthly air temperatures (14°C). These trends are contrary to what would be expected from eDNA decay, dilution or transport, demonstrating that metabarcoding is robust to such influences, reinforcing the interpretation of trends driven by Atlantic salmon ecology and physiology. For example, pH effects reflect beneficial conditions for eggs and perhaps habitat preference for spawners, flow effects reflect the annual return of salmon during higher flows which aid upstream migration, tributary entry and spawning, and, finally, temperature effects reflect higher metabolic rates and greater shedding of eDNA.

P30-60 Grouping and assessment of chemicals for hazard and risk assessment by high content analysis using the zebrafish embryos as an alternative non-sentient animal model - S. Scholz; C. Zanini; A.-K. Koblitz; T. Möller; M.A. Aslam; G.C. Ajugwo; E. Chukwu; J. Colbourne; S. Kader; Q. Fu; N. Grasse; T. Reemtsma; et al. (Toxicology Letters, 2025)

P12-06 Utilising in silico, in vitroand ‘omics New Approach Methodologies (NAMs) for priority-setting and safety assessment of tropane alkaloids as potential food contaminants - A. de Carvalho e Silva; G. Loizou; K. McNally; D. McDonald; S. He; A. Kalian; O. Osborne; C. Potter; J. Colbourne; M. Viant (Toxicology Letters, 2025)

Motor Rehabilitation Provides Modest Functional Benefits After Intracerebral Hemorrhage: a Systematic Review and Meta-Analysis of Translational Rehabilitation Studies - Britt A. Fedor; Noam H. Sander; Maxwell MacLaren; Lane J. Liddle; Crystal L. MacLellan; Frederick Colbourne (Translational Stroke Research, 2025)
Few certainties exist regarding the optimal type, timing, or dosage of rehabilitation after stroke. Despite differing injury mechanisms and recovery patterns following ischemic and hemorrhagic stroke, most translational stroke research is conducted after ischemia. As we enter the era of personalized medicine, exploring subtype-specific treatment efficacy is essential to optimizing recovery. Our objective was to characterize common rehabilitation interventions used after in vivo preclinical intracerebral hemorrhage (ICH) and assess the impact of post-ICH rehabilitation (vs. no-rehabilitation) on recovery of motor function. Following PRISMA guidelines, a systematic review (Academic Search Complete, CINAHL, EMBASE, Medline, PubMed Central) identified eligible articles published up to December 2022. Risk of bias (SYRCLE) and study quality (CAMARADES) were evaluated, and random-effects meta-analysis was used to assess treatment efficacy in recovery of forelimb and locomotor functions. Thirty articles met inclusion criteria, and 48 rehabilitation intervention groups were identified. Most used collagenase to model striatal ICH in young, male rodents. Aerobic exercise, enriched rehabilitation, and constraint-induced movement therapy represented ~ 70% of interventions. Study quality was low (median 4/10, range 2–8), and risk of bias was unclear. Rehabilitation provided modest benefits in skilled reaching, spontaneous impaired forelimb use, and locomotor function; however, effects varied substantially by endpoint, treatment type, and study quality. Rehabilitation statistically improves motor function after preclinical ICH, but whether these effects are functionally meaningful is unclear. Incomplete reporting and variable research quality hinder our capacity to analyze and interpret how treatment factors influence rehabilitation efficacy and recovery after ICH.

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

No Benefit of 3% Hypertonic Saline Following Experimental Intracerebral Hemorrhage - Tiffany F. C. Kung; Anna C. J. Kalisvaart; Angely Claire C. Suerte; Glen C. Jickling; Frank K. H. van Landeghem; Frederick Colbourne (Neurotoxicity Research, 2024)

Multi-omics bioactivity profile-based chemical grouping and read-across: a case study with Daphnia magna and azo dyes - Hanna Gruszczynska; Rosemary E. Barnett; Gavin R. Lloyd; Ralf J. M. Weber; Thomas N. Lawson; Jiarui Zhou; Elena Sostare; John K. Colbourne; Mark R. Viant (Archives of Toxicology, 2024)
Grouping/read-across is widely used for predicting the toxicity of data-poor target substance(s) using data-rich source substance(s). While the chemical industry and the regulators recognise its benefits, registration dossiers are often rejected due to weak analogue/category justifications based largely on the structural similarity of source and target substances. Here we demonstrate how multi-omics measurements can improve confidence in grouping via a statistical assessment of the similarity of molecular effects. Six azo dyes provided a pool of potential source substances to predict long-term toxicity to aquatic invertebrates ( Daphnia magna ) for the dye Disperse Yellow 3 (DY3) as the target substance. First, we assessed the structural similarities of the dyes, generating a grouping hypothesis with DY3 and two Sudan dyes within one group. Daphnia magna were exposed acutely to equi-effective doses of all seven dyes (each at 3 doses and 3 time points), transcriptomics and metabolomics data were generated from 760 samples. Multi-omics bioactivity profile-based grouping uniquely revealed that Sudan 1 (S1) is the most suitable analogue for read-across to DY3. Mapping ToxPrint structural fingerprints of the dyes onto the bioactivity profile-based grouping indicated an aromatic alcohol moiety could be responsible for this bioactivity similarity. The long-term reproductive toxicity to aquatic invertebrates of DY3 was predicted from S1 (21-day NOEC, 40 µg/L). This prediction was confirmed experimentally by measuring the toxicity of DY3 in D. magna . While limitations of this ‘omics approach are identified, the study illustrates an effective statistical approach for building chemical groups.

Intracranial Pressure Dysfunction Following Severe Intracerebral Hemorrhage in Middle-Aged Rats - Anna C. J. Kalisvaart; Ashley H. Abrahart; Alyvia T. Coney; Sherry Gu; Frederick Colbourne (Translational Stroke Research, 2023)
Rising intracranial pressure (ICP) aggravates secondary injury and heightens risk of death following intracerebral hemorrhage (ICH). Long-recognized compensatory mechanisms that lower ICP include reduced cerebrospinal fluid and venous blood volumes. Recently, we identified another compensatory mechanism in severe stroke, a decrease in cerebral parenchymal volume via widespread reductions in cell volume and extracellular space (tissue compliance). Here, we examined how age affects tissue compliance and ICP dynamics after severe ICH in rats (collagenase model). A planned comparison to historical young animal data revealed that aged SHAMs (no stroke) had significant cerebral atrophy (9% reduction, p ≤ 0.05), ventricular enlargement (9% increase, p ≤ 0.05), and smaller CA1 neuron volumes (21%, p ≤ 0.05). After ICH in aged animals, contralateral striatal neuron density and CA1 astrocyte density significantly increased (12% for neurons, 7% for astrocytes, p ≤ 0.05 vs. aged SHAMs). Unlike young animals, other regions in aged animals did not display significantly reduced cell soma volume despite a few trends. Nonetheless, overall contralateral hemisphere volume was 10% smaller in aged ICH animals compared to aged SHAMs ( p ≤ 0.05). This age-dependent pattern of tissue compliance is not due to absent ICH-associated mass effect (83.2 mm 3 avg. bleed volume) as aged ICH animals had significantly elevated mean and peak ICP ( p ≤ 0.01), occurrence of ICP spiking events, as well as bilateral evidence of edema (e.g., 3% in injured brain, p ≤ 0.05 vs. aged SHAMs). Therefore, intracranial compliance reserve changes with age; after ICH, these and other age-related changes may cause greater fluctuation from baseline, increasing the chance of adverse outcomes like mortality.

P22-23: Expediting the uptake of Next-Generation Risk Assessment (NGRA) into EU chemicals legislation under PARC - M. Herzler; I. Apruzzese; N. Bandow; F. Busquet; A. Cavoski; J. Colbourne; E. Di Consiglio; M. Dusinska; G. Flingelli; L. Holden; R. Hornek-Gausterer; A. Kaiser; et al. (Toxicology Letters, 2023)

P06-40: Integrating physiologically-based pharmacokinetic modelling and 'omics data to derive a health-based guidance value for perfluorooctanoic acid - A. de Carvalho e Silva; G. Loizou; K. McNally; J. Colbourne; M. Viant (Toxicology Letters, 2023)

An Ambiguous Role for Fever in Worsening Outcome After Intracerebral Hemorrhage - Lane J. Liddle; Christine A. Dirks; Mohammed Almekhlafi; Frederick Colbourne (Translational Stroke Research, 2023)
Intracerebral hemorrhage (ICH) accounts for 10–15% of all strokes and leaves most survivors with impairments. Fever, a rise in the thermoregulatory set point, complicates ICH. This review summarizes ICH fever studies and employs meta-analytic techniques to explore the relationship between fever and ICH. We discuss methodological considerations for future studies and provide an overview of mechanisms by which fever, and its treatment, may impact ICH. We searched the PubMed database using the following terms: ((fever OR hyperthermia) AND (intracerebral hemorrhage OR intraparenchymal hemorrhage OR intracerebral haemorrhage OR intraparenchymal haemorrhage)). Our search returned 727 studies, of which 21 were included in our final analysis, consisting of 19 clinical, and two preclinical, studies. We conducted a meta-analysis on the clinical data to quantify how fever is related to mortality, functional outcomes, and intraventricular hemorrhage. Analysis of clinical studies suggested that fever causes an increased risk of mortality but does not appear to be associated with poor outcomes among survivors, making it difficult to ascertain the extent of harm caused by post-ICH fever or the benefits of its treatment. Perhaps these inconsistencies stem from variable fever definitions, and temperature measurement and fever treatment protocols. Additionally, the lack of mechanistic data in clinical studies coupled with preclinical studies showing no harmful effects of moderate bouts of hyperthermia raise concerns about the direct contribution of hyperthermia and fever in post ICH outcome. Overall, the significance of temperature increases after ICH is unclear, making this an important area for future research.

Identification of the type locality of the South Island Brown Kiwi Apteryx australis - R. P. Scofield; J. R. Wood; L. de Nascimento; H. A. Robertson; R. M. Colbourne; V. L. De Pietri; J. Innes; J. T. Weir (Conservation Genetics, 2021)

Translational Intracerebral Hemorrhage Research: Has Current Neuroprotection Research ARRIVEd at a Standard for Experimental Design and Reporting? - Lane J. Liddle; Shivani Ralhan; Daniel L. Ward; Frederick Colbourne (Translational Stroke Research, 2020)
One major aim of preclinical intracerebral hemorrhage (ICH) research is to develop and test potential neuroprotectants. Published guidelines for experimental design and reporting stress the importance of clearly and completely reporting results and methodological details to ensure reproducibility and maximize information availability. The current review has two objectives: first, to characterize current ICH neuroprotection research and, second, to analyze aspects of translational design in preclinical ICH studies. Translational design is the adoption and reporting of experimental design characteristics that are thought to be clinically relevant and critical to reproducibility in animal studies (e.g., conducting and reporting experiments according to the STAIR and ARRIVE guidelines, respectively). Given that ICH has no current neuroprotective treatments and an ongoing reproducibility crisis in preclinical research, translational design should be considered by investigators. We conducted a systematic review of ICH research from 2015 to 2019 using the PubMed database. Our search returned 281 published manuscripts studying putative neuroprotectants in animal models. Contemporary ICH research predominantly uses young, healthy male rodents. The collagenase model is the most commonly used. Reporting of group sizes, blinding, and randomization are almost unanimous, but group size calculations, mortality and exclusion criteria, and animal model characteristics are infrequently reported. Overall, current ICH neuroprotection research somewhat aligns with experimental design and reporting guidelines. However, there are areas for improvement. Because failure to consider translational design is associated with inflation of effect sizes (and possibly hindered reproducibility), we suggest that researchers, editors, and publishers collaboratively consider enhanced adherence to published guidelines.

Early transcriptional response pathways in Daphnia magna are coordinated in networks of crustacean‐specific genes - Luisa Orsini; James B. Brown; Omid Shams Solari; Dong Li; Shan He; Ram Podicheti; Marcus H. Stoiber; Katina I. Spanier; Donald Gilbert; Mieke Jansen; Douglas B. Rusch; Michael E. Pfrender; et al. (Molecular Ecology, 2018)
Natural habitats are exposed to an increasing number of environmental stressors that cause important ecological consequences. However, the multifarious nature of environmental change, the strength and the relative timing of each stressor largely limit our understanding of biological responses to environmental change. In particular, early response to unpredictable environmental change, critical to survival and fitness in later life stages, is largely uncharacterized. Here, we characterize the early transcriptional response of the keystone species Daphnia magna to twelve environmental perturbations, including biotic and abiotic stressors. We first perform a differential expression analysis aimed at identifying differential regulation of individual genes in response to stress. This preliminary analysis revealed that a few individual genes were responsive to environmental perturbations and they were modulated in a stressor and genotype‐specific manner. Given the limited number of differentially regulated genes, we were unable to identify pathways involved in stress response. Hence, to gain a better understanding of the genetic and functional foundation of tolerance to multiple environmental stressors, we leveraged the correlative nature of networks and performed a weighted gene co‐expression network analysis. We discovered that approximately one‐third of the Daphnia genes, enriched for metabolism, cell signalling and general stress response, drives transcriptional early response to environmental stress and it is shared among genetic backgrounds. This initial response is followed by a genotype‐ and/or condition‐specific transcriptional response with a strong genotype‐by‐environment interaction. Intriguingly, genotype‐ and condition‐specific transcriptional response is found in genes not conserved beyond crustaceans, suggesting niche‐specific adaptation.

Cryptic inbreeding depression in a growing population of a long‐lived species - Helen R. Taylor; Rogan M. Colbourne; Hugh A. Robertson; Nicola J. Nelson; Fred W. Allendorf; Kristina M. Ramstad (Molecular Ecology, 2017)
Genetic effects are often overlooked in endangered species monitoring, and populations showing positive growth are often assumed to be secure. However, the continued reproductive success of a few individuals may mask issues such as inbreeding depression, especially in long‐lived species. Here, we test for inbreeding depression in little spotted kiwi ( Apteryx owenii ) by comparing a population founded with two birds to one founded with 40 birds, both from the same source population and both showing positive population growth. We used a combination of microsatellite genotypes, nest observations and modelling to examine the consequences of assessing population viability exclusively via population growth. We demonstrate (i) significantly lower hatching success despite significantly higher reproductive effort in the population with two founders; (ii) positive growth in the population with two founders is mainly driven by ongoing chick production of the founding pair; and (iii) a substantial genetic load in the population founded with two birds (10–15 diploid lethal equivalents). Our results illustrate that substantial, cryptic inbreeding depression may still be present when a population is growing, especially in long‐lived species with overlapping generations.

Differential transcriptomic responses of ancient and modern Daphnia genotypes to phosphorus supply - Priyanka Roy Chowdhury; Dagmar Frisch; Dörthe Becker; Jacqueline A. Lopez; Lawrence J. Weider; John K. Colbourne; Punidan D. Jeyasingh (Molecular Ecology, 2015)
Little is known about the role of transcriptomic changes in driving phenotypic evolution in natural populations, particularly in response to anthropogenic environmental change. Previous analyses of Daphnia genotypes separated by centuries of evolution in a lake using methods in resurrection ecology revealed striking genetic and phenotypic shifts that were highly correlated with anthropogenic environmental change, specifically phosphorus (P)‐driven nutrient enrichment (i.e. eutrophication). Here, we compared the transcriptomes of two ancient (~700‐year‐old) and two modern (~10‐year‐old) genotypes in historic (low P) and contemporary (high P) environmental conditions using microarrays. We found considerable transcriptomic variation between ‘ancient’ and ‘modern’ genotypes in both treatments, with stressful (low P) conditions eliciting differential expression ( DE ) of a larger number of genes. Further, more genes were DE between ‘ancient’ and ‘modern’ genotypes than within these groups. Expression patterns of individual genes differed greatly among genotypes, suggesting that different transcriptomic responses can result in similar phenotypes. While this confounded patterns between ‘ancient’ and ‘modern’ genotypes at the gene level, patterns were discernible at the functional level: annotation of DE genes revealed particular enrichment of genes involved in metabolic pathways in response to P‐treatments. Analyses of gene families suggested significant DE in pathways already known to be important in dealing with P‐limitation in Daphnia as well as in other organisms. Such observations on genotypes of a single natural population, separated by hundreds of years of evolution in contrasting environmental conditions before and during anthropogenic environmental changes, highlight the important role of transcriptional mechanisms in the evolutionary responses of populations.

A review of factors contributing to the decline of Newfoundland and Labrador snow crab (Chionoecetes opilio) - Darrell R. J. Mullowney; Earl G. Dawe; Eugene B. Colbourne; George A. Rose (Reviews in Fish Biology and Fisheries, 2014)

A millennial‐scale chronicle of evolutionary responses to cultural eutrophication in Daphnia - Dagmar Frisch; Philip K. Morton; Priyanka Roy Chowdhury; Billy W. Culver; John K. Colbourne; Lawrence J. Weider; Punidan D. Jeyasingh (Ecology Letters, 2014)
For an accurate assessment of the anthropogenic impacts on evolutionary change in natural populations, we need long‐term environmental, genetic and phenotypic data that predate human disturbances. Analysis of c . 1600 years of history chronicled in the sediments of South Center Lake, Minnesota, USA , revealed major environmental changes beginning c . 120 years ago coinciding with the initiation of industrialised agriculture in the catchment area. Population genetic structure, analysed using DNA from dormant eggs of the keystone aquatic herbivore, Daphnia pulicaria , suggested no change for c . 1500 years prior to striking shifts associated with anthropogenic environmental alterations. Furthermore, phenotypic assays on the oldest resurrected metazoan genotypes (potentially as old as c . 700 years) indicate significant shifts in phosphorus utilisation rates compared to younger genotypes. Younger genotypes show steeper reaction norms with high growth under high phosphorus (P), and low growth under low P, while ‘ancient’ genotypes show flat reaction norms, yet higher growth efficiency under low P. Using this resurrection ecology approach, environmental, genetic and phenotypic data spanning pre‐ and post‐industrialised agricultural eras clearly reveal the evolutionary consequences of anthropogenic environmental change.

The evolution of salinity tolerance in Daphnia : a functional genomics approach - Leigh C. Latta; Lawrence J. Weider; John K. Colbourne; Michael E. Pfrender (Ecology Letters, 2012)
One route to genetic adaptation in a novel environment is the evolution of ecological generalisation. Yet, identifying the cost that a generalist pays for the increased breadth of tolerance has proven elusive. We integrate phenotypic assays with functional genomics to understand how tolerance to a salinity gradient evolves, and we test the relationship between the fitness cost of this generalisation and the cost of transcription that arises from evolved differences in patterns of gene expression. Our results suggest that a salt‐tolerant genotype of Daphnia is characterised by constitutively expressed genes, which does not incur a loss of fitness or a cost of transcription relative to a salt‐intolerant genotype in low saline environments. We find that many genes whose expression pattern evolved in response to salinity are also involved in the response to predators, suggesting that the cost of generalisation may be due to trade‐offs along other environmental axes.

Molecular Evolution of Daphnia Immunity Genes: Polymorphism in a Gram-Negative Binding Protein Gene and an ?-2-Macroglobulin Gene - Tom J. Little; John K. Colbourne; Teresa J. Crease (Journal of Molecular Evolution, 2004)

Molecular and other biological evidence supports the recognition of at least three species of brown kiwi - Maryann L. Burbidge; Rogan M. Colbourne; Hugh A. Robertson; Allan J. Baker (Conservation Genetics, 2003)